The use of clinical audit in farm animal veterinary practice in the UK - Waine, K.V. (2017)
Clinical audit was adopted from the medical profession in the late 1990s and is now widely discussed as a quality improvement tool in veterinary medicine. It is suggested by the Royal College of Veterinary Surgeons as a method to improve the care provided to veterinary patients and many opinion pieces offering advice have been published. However, there is no evidence to support its use in farm animal veterinary practice and no understanding of how it is currently used among farm animal practitioners. This PhD thesis aimed to determine if and how clinical audit can be used efficiently and effectively in farm animal veterinary practice in the United Kingdom (UK).